The Tobin tax: A tool for allocative or distributional policies? - Margareta E. Kulessa (Intereconomics, 1996)
The Tobin tax idea, developed during the 1970s as a tax on foreign-exchange transactions, has found its way back into the academic and policy debates, since the Copenhagen World Social Summit and the G7 Summit in early 1995 at the latest. At both events, proposals were put forward to impose a tax on international speculative flows. The purpose of the tax is firstly to prevent destabilising foreign-exchange operations while at the same time acting as a source of revenue. Can the Tobin tax actually live up to these expectations?
Keywords: 330; Speculation